Development of an automated virtual array channel measurement test bed - Tang, Wei (2014)
As the requirements of the degree of Bachelor of Engineering, the student has to accomplish a Final Year Project in 2 semesters. This selected project is development of an automated Virtual Array Channel Measurement Test Bed and is in Tracking and Positioning field. In addition, this project is based on the “Project No: A5166-121 Tracking and Positioning using Dead Teckoning System and Ubiquitious Wireless Signal”.